2019
DOI: 10.1016/j.marchem.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

REE distribution and Nd isotope composition of estuarine waters and bulk sediment leachates tracing lithogenic inputs in eastern Canada

Abstract: The rare earth element (REE) concentrations and the neodymium (Nd) and strontium (Sr) isotope compositions of the detrital fraction and authigenic Fe-Mn oxyhydroxide coatings of marine sediments may provide valuable information for better understanding the pathways of weathering inputs and estuarine and coastal exchange processes on different time scales. Here, we present the REE concentrations and 143 Nd/ 144 Nd (expressed in epsilon units, εNd) and 87 Sr/ 86 Sr ratios of detrital and authigenic (leached Fe-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…Chevis et al [11] suggested that Nd fluxes could be directly influenced by the mineralogy of the sediments and that the released Nd will participate in Fe reduction. On the other hand, Casse et al [37] supported that REE scavenging could be produced by adsorption onto Fe-organic colloids and particulate organic carbon. In the studied Montviel area, Nd also appeared to be anomalously enriched in REE-bearing fluorocarbonates from the carbonatites [15].…”
Section: Unitsmentioning
confidence: 99%
“…Chevis et al [11] suggested that Nd fluxes could be directly influenced by the mineralogy of the sediments and that the released Nd will participate in Fe reduction. On the other hand, Casse et al [37] supported that REE scavenging could be produced by adsorption onto Fe-organic colloids and particulate organic carbon. In the studied Montviel area, Nd also appeared to be anomalously enriched in REE-bearing fluorocarbonates from the carbonatites [15].…”
Section: Unitsmentioning
confidence: 99%
“…The variability in the Hf isotope composition in terrestrial rocks is larger than that in Nd, ranging from the most unradiogenic values of εHf ~ −50 in Archean rocks to values as high as +25 in mid‐ocean ridge basalt (Zimmermann, Porcelli, Frank, Andersson, et al, ). Water masses from different origins therefore acquire distinct regional εNd and εHf signatures derived primarily from riverine continental input, particle‐dissolved exchange processes (a process commonly referred to as boundary exchange), and/or benthic sources (e.g., Abbott et al, ; Casse et al, ; Frank, ; Haley et al, ; Jeandel et al, ; Rickli et al, ; Wilson et al, ; Zimmermann, Porcelli, Frank, Andersson, et al, ; Zimmermann, Porcelli, Frank, Rickli, et al, ). Consequently, Nd and Hf can be used as sensitive tracers for both (1) water mass mixing and provenance (Chen et al, ; Rickli et al, ; Stichel et al, ), because both elements' oceanic residence times are shorter than the oceanic mixing time (approximately 1,500 years; Frank, ), and (2) detrital provenance changes and continental weathering intensity (Gutjahr et al, ; Rickli et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Nd and Hf can be used as sensitive tracers for both (1) water mass mixing and provenance (Chen et al, ; Rickli et al, ; Stichel et al, ), because both elements' oceanic residence times are shorter than the oceanic mixing time (approximately 1,500 years; Frank, ), and (2) detrital provenance changes and continental weathering intensity (Gutjahr et al, ; Rickli et al, ). Because dissolved trace elements are incorporated by coprecipitation processes during early burial in the top few centimeters of the sediments (Bayon et al, ; Haley et al, ), the authigenic Nd and Hf signatures can be extracted from ferromanganese (Fe‐Mn) oxyhydroxide coatings on marine sediment samples (Bayon et al, ; Casse et al, ; Chen et al, ; Gutjahr et al, ). Based on these findings, the analysis of ɛNd and ɛHf signatures of authigenic fractions in marine sediments is a powerful tool for assessing late Quaternary changes in water mass provenance and in pathways of weathering inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Trace element concentrations (e.g., Th, U, Y, Sc, Cr, Co, Ni, V, and REE) in clastic sediments are more reliable indicators of provenance than major elements and are extensively applied in various studies to infer sediment provenance (e.g., Basu 2017;Zhang et al 2018;Casse et al 2019). This is because incompatible trace elements are concentrated in sediments derived from felsic igneous rocks, whereas compatible elements are enriched in sediments derived from mafic igneous rocks and their weathered products.…”
Section: Source Rock Composition and Tectonic Settingmentioning
confidence: 99%
“…1 Map showing the geology and geography of Riachuelos and Palma Sola beach areas, Gulf of Mexico (Source: Carta Geológica; Scale: 1:1,000,000; modified after Anaya-Gregorio et al 2018). L. = Lagoon; R. = River literature (Basu et al 2016;Carranza-Edwards et al 2019;Casse et al 2019;Karudu 2019;Men et al 2019;Kettanah et al 2020). Although clastic sediments are affected by factors such as weathering, diagenesis, and mineral fractionation during transport, their mineralogical-geochemical composition is mainly related to the parent rock types and the influence factors of the source (McLennan et al 1993;Basu 2017;Ramos-Vázquez et al 2017Bansal et al 2018;Ndjigui et al 2019;Rivera-Gómez et al 2020).…”
Section: Introductionmentioning
confidence: 99%